Optimal electrical stimulation boosts stem cell therapy in nerve regeneration - Du, Jian; Zhen, Gehua; Chen, Huanwen; Zhang, Shuming; Qing, Liming; Yang, Xiuli; Lee, Gabsang; Mao, Hai-Quan; Jia, Xiaofeng (Biomaterials, 2018)
Peripheral nerve injuries often lead to incomplete recovery and contribute to significant disability to approximately 360,000 people in the USA each year. Stem cell therapy holds significant promise for peripheral nerve regeneration, but maintenance of stem cell viability and differentiation potential in vivo are still major obstacles for translation. Using a made-in-house 96-well vertical electrical stimulation (ES) platform, we investigated the effects of different stimulating pulse frequency, duration and field direction on human neural crest stem cell (NCSC) differentiation. We observed dendritic morphology with enhanced neuronal differentiation for NCSCs cultured on cathodes subject to 20 Hz, 100μs pulse at a potential gradient of 200 mV/mm. We further evaluated the effect of a novel cell-based therapy featuring optimized pulsatile ES of NCSCs for in vivo transplantation following peripheral nerve regeneration. 15 mm critical-sized sciatic nerve injuries were generated with subsequent surgical repair in sixty athymic nude rats. Injured animals were randomly assigned into five groups (N = 12 per group): blank control, ES, NCSC, NCSC + ES, and autologous nerve graft. The optimized ES was applied immediately after surgical repair for 1 h in ES and NCSC + ES groups. Recovery was assessed by behavioral (CatWalk gait analysis), wet muscle-mass, histomorphometric, and immunohistochemical analyses at either 6 or 12 weeks after surgery (N = 6 per group). Gastrocnemius muscle wet mass measurements in ES + NCSC group were comparable to autologous nerve transplantation and significantly higher than other groups (p < 0.05). Quantitative histomorphometric analysis and catwalk gait analysis showed similar improvements by ES on NCSCs (p < 0.05). A higher number of viable NCSCs was shown via immunochemical analysis, with higher Schwann cell (SC) differentiation in the NCSC + ES group compared to the NCSC group (p < 0.05). Overall, ES on NCSC transplantation significantly enhanced nerve regeneration after injury and repair, and was comparable to autograft treatment. Thus, ES can be a potent alternative to biochemical and physical cues for modulating stem cell survival and differentiation. This novel cell-based intervention presents an effective and safe approach for improved outcomes after peripheral nerve repair.